Recognition-German idealism as an ongoing challenge - Krijnen, Christian. (Critical Studies in German Idealism, 2014)
There has been an intensive debate in recent years, particularly in political philosophy, on how the concept of recognition ( Anerkennung) can bring insight into understanding social and political relationships and answering ethical questions. Proponents of this philosophy seek to apply German Idealism, especially Hegel, to the arguments of recognition in order to solve contemporary problems. However, does the present debate incorporate sufficiently the requirements of the idealist philosophy which it pretends to inherit and update? As a new paradigm for philosophy claiming to actualize German idealist philosophy, it provokes questions about the foundation of the principle of recognition itself as well as about which philosophical method provides the best means for addressing recognition. In Recognition -- German Idealism as an Ongoing Challenge , renowned authors address this fascinating and far-reaching questions in discussion with Kant, Fichte, Schelling and Hegel. Contributors include: Robert Brandom, Paul Cobben, Simon Critchley, Pirmin Stekeler-Weithofer, Kenneth Westphal, Klaus Vieweg, Erzsébet Rósza, Christian Krijnen, Heikki Ikäheimo, Donald Loose, Kurt Walter Zeidler, Jean-Christophe Merle, Sasa Josifovic, Arthur Kok, Emiliano Acosta